Student's Perception and Expectation of Guidance and Counseling in Padang 2 High School - Arima Ansari; Mudjiran Mudjiran (Universitas Negeri Padang, 2021)
Perception is the process thinking of a person in giving meaning to the stimulus he receives through the five senses, while hope is the ability to plan a way out in an effort to achieve goals even though there are obstacles and make motivation as a way of achieving goals. This study aims to describe students' perceptions and expectations of BK. This research uses a descriptive approach with quantitative methods. The sample in this study was class X, XI, XII SMA Negeri 2 Padang, totaling 330 students. The data collection tool used was a questionnaire. The data analysis technique used descriptive statistical analysis. The findings of this study as a whole indicate that students 'perceptions of BK services at SMA Negeri 2 Padang based on the aspects of the BK service function are in the good category with a percentage of 63.33% and students' perceptions of BK services at SMA N 2 Padang based on the aspects of BK service objectives are at quite good category with a percentage of 48.79%. Furthermore, students 'expectations for BK services at SMA Negeri 2 Padang based on the time aspect of BK service implementation were in the good category with a percentage of 64.24% and students' expectations for BK services at SMA Negeri 2 Padang based on the counselor's personality aspects were in the good category with a percentage of 59 39%. Based on the research findings, it is suggested to counseling teachers in order to be able to continuously improve the performance of counseling teachers who are more creative and innovative in providing BK services and continue to monitor student development so that good perceptions and expectations can be even better through services carried out by BK teachers.